Biological properties of the BCL-2 family protein BCL-RAMBO, which regulates apoptosis, mitochondrial fragmentation, and mitophagy - Kataoka, Takao (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria play an essential role in the regulation of cellular stress responses, including cell death. Damaged mitochondria are removed by fission and fusion cycles and mitophagy, which counteract cell death. BCL-2 family proteins possess one to four BCL-2 homology domains and regulate apoptosis signaling at mitochondria. BCL-RAMBO, also known as BCL2-like 13 (BCL2L13), was initially identified as one of the BCL-2 family proteins inducing apoptosis. Mitophagy receptors recruit the ATG8 family proteins MAP1LC3/GABARAP via the MAP1LC3-interacting region (LIR) motif to initiate mitophagy. In addition to apoptosis, BCL-RAMBO has recently been identified as a mitophagy receptor that possesses the LIR motif and regulates mitochondrial fragmentation and mitophagy. In the twenty years since its discovery, many important findings on BCL-RAMBO have been increasingly reported. The biological properties of BCL-RAMBO are reviewed herein.